The impact of the adoption of international accounting and auditing standards on corruption perception - Kurniawati, Elisabeth Penti; Achjari, Didi (Emerald Publishing, 2022)
Purpose: This study aims to investigate the impact of the adoption of international accounting and auditing standards on corruption perception. In addition, this study examines the strength of auditing and reporting standards (SARS) that mediate the relationship. Design/methodology/approach: Agency theory and bonding theory were applied in this paper to investigate the impact of the adoption of international accounting and auditing standards on corruption perception. Data from 130 countries during three years were collected from Transparency International, Worldwide Governance Indicators, International Federation of Accountants, World Economic Forum, World Bank, Freedom House and World Justice Project. Hypotheses were tested using partial least squares structural equation modeling. Findings: The results show a positive impact of the adoption of international accounting and auditing standards on corruption perception, directly and indirectly, through the SARS. Practical implications: The results provide an insight into corruption eradication strategy through the adoption of international accounting and auditing standards and strengthen the auditing and reporting standards. Originality/value: This study is distinctive, as no study has yet examined the impact of the adoption of international accounting standards construct, which contains International Financial Reporting Standards and International Standards on Auditing, on the corruption perception. The corruption perception construct is developed by combining the corruption perception index and the control of corruption indicators. © 2022, Emerald Publishing Limited.